A systematic review of case-series studies on the effectiveness of interventions to reduce polypharmacy and its adverse consequences in the elderly. - Maria Benedetta Michelazzo; Sonja Milovanovic; Stefania Boccia (Epidemiology, Biostatistics and Public Health)
Background. Aging is frequently accompanied by chronic diseases; as a consequence, older people are often exposed to polypharmacy that has been associated with negative health-consequences. The aim of this study is to conduct a systematic review of the literature reporting on the effectiveness of different approaches to reduce polypharmacy in the elderly.